Numerical investigation of springback in mechanical clinching process - Eshteyah, Mohanna Moh'd Saleem; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (2017)
In this work, a numerical investigation was conducted to study the springback phenomena in the mechanical clinching process. The springback values were calculated using finite element simulations and it was found that these values depend strongly on the strength of the materials. A Taguchi optimization method was used to determine the optimal parameters affecting springback. However, in the case of materials with low tensile strength, determining parameters affecting springback becomes difficult. Implicit and explicit simulations of clinching joints using the springback analysis show that the distance between the joint sheets becomes almost zero after stress recovery.